Assessment of the Nursing Quality Indicators for Reporting and Evaluation (NQuIRE) database using a data quality index. (2nd May 2020) - Naik, Shanoja; Voong, Stephanie; Bamford, Megan; Smith, Kyle; Joyce, Angela; Grinspun, Doris
Abstract: A comprehensive data quality assessment is necessary to expand a nursing database that is designed for evaluating the impact of implementing Best Practice Guidelines (BPG) developed by the Registered Nurses' Association of Ontario (RNAO). This case report presents a method to standardize data quality assessments of the Nursing Quality Indicators for Reporting and Evaluation (NQuIRE) database by developing a data quality framework (DQF) and assessing key dimensions of the framework using a data quality index (DQI). The data quality index is a single key performance metric for assessing the quality of the database. The aims of sharing this case report are 2-fold: (1) to promote best practices for assessing data quality by developing and implementing a data quality framework and (2) to demonstrate an unprecedented method of assessing the data quality of a nursing database.